Al-Dzari'ah Analysis of the Circular Letter of the Directorate General of Islamic Community Guidance Number 06 of 2020 concerning COVID-Safe Marriage Services - Faiz Nashrullah; Maratus Shalikhah (Media Syari'ah, 2021)
The emergence of the coronavirus outbreak impacts the changes in life order in Indonesia, not least on the implementation of marriage covenants. The government changed the marriage procedure as regulated in the Circular Letter of the Directorate General of Islamic Community Guidance No. 06 of 2020 on Marriage Services Towards a Covid-Safe Productive Society. The purpose of this Circular is to reduce the risk of coronavirus transmission. However, the regulation is considered not optimal in minimizing the occurrence of crowds and still causes many transmissions from marriage clusters. This research is library research using two approaches, namely the statute approach and the conceptual approach. The author analyses the regulations in the Circular using the al-dzariah concept to find out whether the circular letter has closed the covid transmission path or not. The result of this study suggests that the circular letter still opens up opportunities for the spread of the Covid-19 virus and has a mafsadah impact on the community, so it is included in the category of sadd al-dzariah. Articles 5 and 6 states that a maximum of 10 people may attend if the marriage is held inside the KUA (Religious Affair Office) and 30 people outside the KUA. The number can be minimized to 6 people without hindering the validity of the marriage, either according to Islamic law or positive law.